The role of the ASEAN tourism forum (ATF) in supporting Indonesian tourism - Adesty Lasally; Lutfi Handayani; Samsul Arifin (Journal of Gastro Tourism, 2023)
This study aims to analyze the role of ASEAN Tourism Forum (ATF) in supporting tourism in Indonesia. Research methods are carried out qualitatively by collecting data through literature studies. The analysis uses Miles Huberman's analysis which includes data collection, data reduction, data presentation, and drawing conclusions. The results showed that the ATF has played a role in the development of tourism in Indonesia. Some of the roles that have been carried out by ATF are (1) ATF acts as a tourism promoter (Tourism Marketing Strategic (ATMS) to market the Wonderful Indonesia brand), (2) ATF acts as an investment cooperation forum (promotion of Indonesian tourism investment), (3) ATF acts as a tourism standardization forum (standards for green hotels, Food and Beverage, Public Restroom, Homestay, Ecotourism and Tourism Heritage), (4) ATF plays a role in increasing tourist visits in Indonesia by giving awards for the best destinations to boost the prestige of Indonesian tourism, and (5) ATF organizing TRAVEX (Travel Exchange) to boost economically profitable transactions.